Energy Saving Retrofitting of Existing Public Building: A Case Study in Shanghai Area. Issue 1 (March 2021) - Qu, Y
Abstract: In order to reduce energy consumption of commercial and public buildings, a series of policies has been implemented in Shanghai area. And retrofitting of inefficient commercial and public buildings serves as one of the main measures. However, there is little study about the effect and economic analysis of energy saving retrofitting, which hinders the popularizing of energy saving retrofitting. Under the sponsorship of the government of Shanghai and World Bank, a typical office building in Changning district of Shanghai was studied about whether it could be retrofitted into a nearly zero energy building through a series of passive and active technologies. During the design stage, based on energy consumption simulations, it was found that nearly zero energy building could save 37.1% energy compared with baseline building. Among the adopted technologies, high-efficiency lamp and photovoltaic system had a relatively higher energy saving ratio, which were followed by high-efficiency cooling and heating system, natural lighting and envelope insulation. Natural ventilation had the least energy saving ratio. By one-year field monitoring of energy consumption after building retrofitting, it was found that the retrofitted building was able to control the CO2 emission per unit area to be less than 25 kg/m2 · a, which met the goal of nearly zero energy building. And the incremental cost per unit area of nearly zero energy building is ￥1553 compared to baseline building. High efficiency lighting is the most cost-effective technology. The conclusions drawn in this study could provide reference for similar retrofitting projects in Shanghai area.